2021
DOI: 10.2298/vsp190119040p
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute and chronic Red Bull® consumption on cardiodynamics and oxidative stress in coronary effluent of trained rats

Abstract: Background/Aim. Energy drinks (EDs) are widely used by athletes as ergogenic agents. The aims of this study were to determine the acute and chronic effects of Red Bull ® , one of the most consumed EDs, on cardiodynamics and parameters of oxidative stress in physically trained rats. Methods. Rats were subjected to a swimming practice (1h per day, 5 days a week, during 4 weeks). They were divided into 4 groups: rats that did not consume ED either before swimming or prior to sacrificing; rats that did not consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In that paper, we have shown that, in trained rats, acute consummation of the RB had a positive inotropic effect (manifested as significantly higher level of dp/dt max and dp/dt min compared to the levels measured in control rats), while chronic administration affected the isolated increase in SLVP, which could be considered the potentially negative impact chronic ED consumption (42). There were no significant differences in cardiodynamic parameters after acute RB consummation (30min before sacrificing) between trained rats that regularly drank RB and those who did not (42), which is in consent with the results presented in this pa-per (direct instead of acute RB administration). Those results suggest that acute/direct RB administration affects cardiodynamics to the greater extent in untrained, than in trained rats, i.e.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In that paper, we have shown that, in trained rats, acute consummation of the RB had a positive inotropic effect (manifested as significantly higher level of dp/dt max and dp/dt min compared to the levels measured in control rats), while chronic administration affected the isolated increase in SLVP, which could be considered the potentially negative impact chronic ED consumption (42). There were no significant differences in cardiodynamic parameters after acute RB consummation (30min before sacrificing) between trained rats that regularly drank RB and those who did not (42), which is in consent with the results presented in this pa-per (direct instead of acute RB administration). Those results suggest that acute/direct RB administration affects cardiodynamics to the greater extent in untrained, than in trained rats, i.e.…”
Section: Discussionmentioning
confidence: 91%
“…As we have previously mentioned, there are no other studies that included administration of ED directly to the isolated rat heart, except for the study that has been recently published by our team (42). In that paper, we have shown that, in trained rats, acute consummation of the RB had a positive inotropic effect (manifested as significantly higher level of dp/dt max and dp/dt min compared to the levels measured in control rats), while chronic administration affected the isolated increase in SLVP, which could be considered the potentially negative impact chronic ED consumption (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations